La ciudad en la poesía de Augusto de Campos: del conjuro y la ciudad-falansterio a la ciudad moderna pero babélica - Gerardo Jorge (Confluenze, 2011)
This paper presents an analysis of the city’s image constructed in the work of brazilian poet Augusto de Campos, beginning with a poem from 1963, “cidade / city / cité”, and through works from the year 2000 as “sem saída”. Using concepts as “modern city”, “babelic city” and “phalanstery city”, this paper will approach the author’s conception of the relationship between poetry, city and politics, and the way it mutes. Finally, the article will raise critical views of Brazil’s modern image, emerged in the late sixties, and it will be revised De Campos’s intervention in this context.